Baby Watch: Capitalism, Technology, and the History of Maternal Privacy and Livestreamed Surveillance in Captive Animal Spaces - Ringer, Andrea (Privacy Studies Journal, 2026)
Baby animals, which were first included in zoo populations as a novel financial windfall, are now the lifeblood of these captive spaces pushing their own image as conservators of species. The notion of privacy was something that captive animal mothers throughout the history of zoos did not experience, as keepers learned by experience to determine which birthing environments provided higher rates of infant survival throughout the twentieth century. While the first generation of mothers gave birth with visitors and zookeepers often keeping close watch, best practices changed as video surveillance allowed the illusion of privacy. However, even as pregnant animal mothers were given more notions of privacy away from the prying eyes of visitors or many keepers, zoos began keeping a closer eye on the birthing process, even if from a distance on a camera. Although mother animals in zoos have increasingly been placed in birthing environments more conducive to their physical well-being, the intersection of technology and capitalism has ensured that captive spaces afford even less privacy to them than in previous decades. This paper explores the history of animal births in captive spaces, from accredited zoos to private safaris in the US, and the ways that privacy—or the impression of privacy—has played a role in each of these experiences.